1981
DOI: 10.1111/j.1540-5915.1981.tb00106.x
|View full text |Cite
|
Sign up to set email alerts
|

PRODUCTION/OPERATIONS MANAGEMENT: AGENDA FOR THE '80s*

Abstract: It is customary at the beginning of a new decade to take stock, to assess the past, and to anticipate the future. Stock-taking discussions among production/ operations management (P/OM) specialists reveal the field to be at a critical point in its evolution. Just a few years ago many of us believed that P/OM had not gained the professional credibility accorded to other functionally related disciplines. Further efforts along the lines then being pursued seemed to hold small promise for improving the situation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
3

Year Published

1983
1983
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(47 citation statements)
references
References 3 publications
0
44
0
3
Order By: Relevance
“…Reviews of the content of operations management were conducted by a number of people including Buffa (1980) and Voss andnrds .,...,- Voss (1980) (1 984) and in the UK, the International Journal of Operations and Production Management. This strengthening of the identity of operations management in the 1980s led to a number of groups reviewing and developing the research agendas for the area (Chase 1980;Miller et al, 1981;Voss, 1984). Both Miller in the US and Voss in the UK developed very similar agendas; these are summarized in Table 2.…”
Section: Operations Management -An Historical Perspectivementioning
confidence: 95%
“…Reviews of the content of operations management were conducted by a number of people including Buffa (1980) and Voss andnrds .,...,- Voss (1980) (1 984) and in the UK, the International Journal of Operations and Production Management. This strengthening of the identity of operations management in the 1980s led to a number of groups reviewing and developing the research agendas for the area (Chase 1980;Miller et al, 1981;Voss, 1984). Both Miller in the US and Voss in the UK developed very similar agendas; these are summarized in Table 2.…”
Section: Operations Management -An Historical Perspectivementioning
confidence: 95%
“…Over the decades, there have been many qualitative studies that attempted to identify the major knowledge groups in OM (Meredith, 1979;Buffa, 1980;Chase, 1980;Miller et al, 1981;Mabert, 1982;Hill et al, 1988Hill et al, -1989Amoako-Gyampah and Meredith, 1989;Meredith and Amoako-Gyampah, 1990;Neely, 1993;Voss, 1984;Scudder and Hill, 1998;Pannirselvan et al, 1999;Gupta et al, 2006). Most of them, however, were focused on a particular journal, setting (manufacturing, services, practice), research method, or type of outlet (e.g., dissertations).…”
Section: Literature Reviewmentioning
confidence: 96%
“…For example, Miller and Graham (1981) synthesized the thoughts of a number of OM faculty in setting an agenda that called for OM researchers to leave their offices more often to observe the world around them and to address broader issues. Observing that OM researchers had little experience with such an approach, the authors suggested collaboration with researchers from other areas, particularly organizational behavior and business policy (p. 568).…”
Section: Peter T Wardmentioning
confidence: 99%